2009
DOI: 10.7547/0980191
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shockwave Therapy for Interdigital Neuroma

Abstract: Extracorporeal shockwave therapy is a possible alternative to surgical excision for Morton's neuroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…A few studies have tried to apply ESWT as an alternative management for treating peripheral neuropathy, for example interdigital neuroma28, stump neuroma29, distal symmetric polyneuropathy30, and CTS131415, with inspiring results. In 2013, Seok et al 13.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have tried to apply ESWT as an alternative management for treating peripheral neuropathy, for example interdigital neuroma28, stump neuroma29, distal symmetric polyneuropathy30, and CTS131415, with inspiring results. In 2013, Seok et al 13.…”
Section: Discussionmentioning
confidence: 99%
“…In another study [16], 25 patients (25 feet) were recruited and consented to take part in a placebo-controlled and blinded study to evaluate the efficacy and safety of ESWT to ablate clinically confirmed Morton's neuroma. The active group was treated using a OssaTron device (HealthTronics, Austin, TX, USA) using 2,000 pulses delivered at 21 kV inferior to the neuroma.…”
Section: Discussionmentioning
confidence: 99%
“…8 Extracorporeal shock wave therapy is also used in the treatment of different diseases, such as peripheral neuropathies, interdigital neuroma, and symmetric polyneuropathy. 9,10 Extracorporeal shock wave therapy has been investigated and used as a new method in the treatment of CTS. [5][6][7] Extracorporeal shock wave therapy stimulates nitric oxide (NO) production by stimulating neurogenesis, angiogenesis, and neuronal NO synthase using vascular endothelial growth factor.…”
Section: What Is Newmentioning
confidence: 99%